Inter- and intraspecific variation of breeding biology, movements, and genotype in Peregrine Falcon Falco peregrinus and Gyrfalcon F. rusticolus populations in Greenland - Burnham, K (2007)
Peregrines Falco peregrinus and Gyrfalcons F. rusticolus were studied in Low and High Arctic Greenland, comparing populations within and between areas. Analyses of weather data from northwest Greenland (1979–2005) revealed a general warming trend, resulting in a lengthened breeding window for many bird species. Both falcon species depend on cliffs for nesting, and take a similar range of bird species as prey. However, Gyrfalcons lay six weeks earlier than Peregrines in Kangerlussuaq and one month earlier than Peregrines in Thule, and occupy more sheltered nest-sites. Being larger than Peregrines, Gyrfalcons also take some larger prey species. In addition, both species move to lower latitudes for the winter, but while most Gyrfalcons migrate relatively short distances, Peregrines are complete long-distance migrants to Central and South America. One Peregrine, satellite-tracked from its breeding site at 76.5° N, travelled ~12,500 km and >100° in latitude, one of the longest migrations ever documented for a raptor. Around Thule in northwest Greenland (at 76.5° N), scientists had historically documented no breeding Peregrines, but six occupied sites were discovered during this study, comprising what is probably the most northern nesting population in the world. Over the same period, breeding Gyrfalcons have apparently disappeared from southern Greenland, and may have declined in central-west Greenland (67° N). The ultimate cause of this retraction may be climate warming, but the proximate cause is probably competition from an increasing Peregrine population. Gyrfalcons tagged with satellite-received transmitters showed characteristics associated with both obligate and facultative migration. Their winter ranges varied greatly in size, with the largest, ~172,000 km2, being the biggest ever documented for a raptor. Many individuals made long movements within a winter, and some spent up to a month at sea. They may have rested on ice and fed upon seabirds. Carbon dating of stratified faecal accumulation from Gyrfalcon nests in central-west and northwest Greenland showed use of sites for up to ~2,500 and ~650 years, respectively. The age of nest sites correlated significantly with the current distance to the Greenland Ice Sheet, and probably reflects colonization patterns following glacial retreat. In central-west Greenland the ratio of Peregrine to Gyrfalcon pairs changed from 1:1 in the early 1970s to nearly 14:1 in 2005. Over this period, competition for nest sites and prey is likely to have intensified. The crucial prey for Gyrfalcons when they start nesting in early spring are resident ptarmigan, whose numbers are probably depleted by Peregrines during the months they are present. If recent trends in climate change continue, Peregrines may continue to increase in Greenland, and spread north into areas previously occupied only by Gyrfalcons. At the same time, Gyrfalcons may retreat north from many currently-occupied areas.